PEMERIKSAAN STATUS GIZI DAN PENGENALAN SARAPAN SEHAT PADA SISWA SDN No. 1 TIANYAR BARAT KUBU KARANGASEM - G N. Indraguna P; IB Wirakusuma; M. Dharmadi; A.A. S Sawitri; P. Cintya D.Y (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2013)
Efforts to improve the quality of human resources began with fulfilling their basic needs. Nutritional statusis one indicator of the quality of human resources, especially in children of school age. Karangasem regency hadthe highest prevalence of underweight children in Bali. Based on the results of rapid survey of 10 children in theElementary School no.1 of West Tianyar showed 2 (20%) students was underweight and only 1 of 10 childrenare said to usually take breakfast at home. Based on these, the initial thing that can be done is by detecting thenutrition status and socialization healthy breakfast at school. Socialization was conducted for 34 students in grade4, 5 and 6 with teaching method. Nutritional status was examined from 31 students in grade 1,2 and 3. Themeasurement results were analyzed by the CDC Growth Charts for Children to assess the nutritional status ofeach student. The socialization went well and there was the improving knowledge about22.32%.The examinationof nutritional status showed that the malnutrition status 14.3% in males and 17.6% in females. These activitieswere an initial way to improve the students’ knowledge whom are expected to continue their behavior of healthynutrition at home. Ongoing activities are expected to monitor the nutritional status and children development,especially in Tianyar West village.